Effectiveness of Savings and Loans Business Unit Management by Village-Owned Enterprises (BUMDES) in Bubalango Village, East Sumalata District, North Gorontalo Regency - Rianti Poneta; Rachman, Ellys; Gintulangi, Sabriana Oktaviana (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the effectiveness of managing savings and loan business units by village-owned enterprises (BUMDES) in Bubalango Village, East Sumalata District, North Gorontalo Regency. The focus in this research is planning, knowledge, and capital. The research method uses a descriptive qualitative approach. Data collection techniques were carried out through in-depth interviews with a number of informants, observation and recording secondary data related to the research problem. The results of the research concluded that the management planning carried out by BUMDES administrators has not been implemented maximally, the knowledge possessed by BUMDES administrators is still lacking in terms of education and experience in managing village-owned enterprises and the capital obtained in managing BUMDES comes from Village Fund Allocations and government assistance. area to meet community needs in providing business capital in Bubalango Village, East Sumalata District.